A trial on the Effects of Life Style Interventions in High-Normal Blood Pressure - Choudhury, KN; Mahmud, RS; Salehuddin, M; Zareen, S; Uddin, SN; Ghosh, SK (Cardiovascular Journal, 2010)
Background: This experimental (Intervention) study was conducted with objective of evaluating the outcome of non-pharmacological approach (lifestyle intervention) through reducing the modifiable risk factors on high normal blood pressure or pre-hypertension (systolic blood pressure130- 139mm of Hg and diastolic blood pressure 85-89 mm of Hg).The study was provided risk reduction management intervention was given on subjects of high normal blood pressure through adequate physical activity, tobacco cessation, dietary advice for unhealthy to healthy diet, reduction of salt intake, reduction of over weight & stress management etc. Materials and methods: The study was conducted among 434 respondents aged 30 -50 years during the period from June 2008 to May 2009 with intervention for 6 months.Random sampling, those cases were fulfilled the inclusion and exclusion. High-normal BP were found out through BP measurement & clinical examination then sample population were selected by randomization: odds numbers in study group (intervention group) and even numbers in control group (comparision group). After obtaing informed consent data were collected by interview, clinical examination, anthropometric measurement and investigations. It was three phases, first phase were case identification & intervention for study group, second phase was follow up and third phase was outcome measurement for both groups. Cases were hold a record card with contact number. Results: After six month mean difference of blood pressure, lipid profile, weight were changed both the groups but changed was significant in the study group. Mean systolic blood pressure reduced 4.1±6.0 in the study group and 1.2±6.4 in the control group,(p< 0.001). Mean diastolic pressure reduced 3.5±4.9 in study group and 1.2±6.4 in control group (p<0.001). Mean total cholesterol, LDL cholesterol and triglycerides decreased in the study group 19.7±18.6, 10.6±14.6 and 15.4 ±21 respectivley and in control group mean of all these parameters decreased to 11.5±16.5, 5.1±12.9 and 6.7±23.2 respectively. Mean HDL cholesterol for men and women in the study group was raised to 5.6±5.9 and 4.5± 6.4 respectively (p<0.001). Mean weight reduced 1.94±1.59 in study group and 0.06±1.44 in the control group (p<0.001). Conclusion: The final outcome of the study was that mean high normal blood pressure was found to reduced due to intervention of non- pharmacological management. So, If we encourages subjects after 40 years for routine health check up in hospital setting & service for risk factor detection & management (preventive cardiology), we will reduce the risk factors of high normal blood pressure (pre-hypertension) & cardiovascular diseases to some extent. Encourages population to stay with normal blood pressure & healthy life style. Keywords: High-normal blood pressure; Pre-hypertension; Life style modification; Nonpharmacological intervention. DOI: 10.3329/cardio.v2i2.6639 Cardiovasc. j. 2010; 2(2) : 195-203